2010
DOI: 10.1186/1743-422x-7-272
|View full text |Cite
|
Sign up to set email alerts
|

Human parvovirus PARV4 DNA in tissues from adult individuals: a comparison with human parvovirus B19 (B19V)

Abstract: BackgroundPARV4 is a new member of the Parvoviridae family not closely related to any of the known human parvoviruses. Viremia seems to be a hallmark of PARV4 infection and viral DNA persistence has been demonstrated in a few tissues. Till now, PARV4 has not been associated with any disease and its prevalence in human population has not been clearly established. This study was aimed to assess the tissue distribution and the ability to persist of PARV4 in comparison to parvovirus B19 (B19V).ResultsPARV4 and B19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
3
18
0
1
Order By: Relevance
“…A much lower PARV4 DNA detection rate in blood donors in France may explain the result. Inconsistent with the fi ndings of extremely low seroprevalence in France and the United Kingdom, PARV4 DNA was detected in the liver (15% and 41%, respectively) and the heart (41%) of non-HIV-infected patients in Germany (11) and Italy (14). PARV4 infection might be more widespread in some countries in Europe.…”
Section: Discussionsupporting
confidence: 58%
“…A much lower PARV4 DNA detection rate in blood donors in France may explain the result. Inconsistent with the fi ndings of extremely low seroprevalence in France and the United Kingdom, PARV4 DNA was detected in the liver (15% and 41%, respectively) and the heart (41%) of non-HIV-infected patients in Germany (11) and Italy (14). PARV4 infection might be more widespread in some countries in Europe.…”
Section: Discussionsupporting
confidence: 58%
“…The absence of PARV4 in these immunocompromised patients is in agreement with the recent study by Tolfvenstam et al and with the previous studies reporting PARV4 appearing to be primarily blood-borne in Northern Europe, but could possibly also reflect a lower prevalence in Northern Europe. 38,[41][42][43][44]47 It has been found among infants in West Africa with no evidence of parenteral exposure. 35,36 Pediatric patients with HSCT J Rahiala et al…”
Section: Discussionmentioning
confidence: 99%
“…6,[34][35][36] The viral DNA has been shown to persist in lymphoid and some other tissues. [37][38][39][40][41] The virus is most frequently detected in persons with a history of i.v. drug use or as co-infections with other parenterally transmitted viruses, such as HIV or hepatitis C and B.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers that conducted a study in Taiwan suggested placental transmission (12). So far, the virus has been isolated from many tissues including bone marrow of HIV-positive individuals (13) and the liver of HBVand HCV-infected patients (14,15). Moreover, the virus has been diagnosed in plasma, cerebrospinal fluid (CSF), skin, myocardium, and blood products around the world (1,3,7,8,11,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the virus has been isolated from many tissues including bone marrow of HIV-positive individuals (13) and the liver of HBVand HCV-infected patients (14,15). Moreover, the virus has been diagnosed in plasma, cerebrospinal fluid (CSF), skin, myocardium, and blood products around the world (1,3,7,8,11,(15)(16)(17). Despite the detection of viral nucleic acid in many organs, PARV4 has scarcely been linked to specific symptoms, except for a recent study that was conducted in Africa linking PARV4 to encephalitis (11) and another study in which the virus was diagnosed in people with symptoms including pharyngitis, nausea, and joint pain (1).…”
Section: Introductionmentioning
confidence: 99%